Pelatihan peningkatan kemampuan menulis huruf Hijaiyah bagi anak usia dini di TPQ BAITURRAHMAN - Wapa, Andi; wijaksono, agus; Hasanah , Uswatun; Uddin , Achmad Faruq Dzia (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Community service through a mentoring program for writing hijaiyah letters at TPQ Baiturrahman. Education is a form of conscious effort to change circumstances. From not knowing to knowing. Education has an important role, especially in the progress of the nation. Education is the main center in the formation of national cadres. No exception for religious education. Religious education is an important education for every individual. Learning activities at TPQ are relatively the same as Islamic boarding schools. The difference is that if at TPQ students leave from home, then at Islamic boarding schools students are domiciled. The PKM method used in the study uses the INPO method, namely (input-process-output). The INPO method is divided into three stages, namely the input stage, the process stage, and the output stage. The INPO method is a method that combines field research with qualitative and quantitative, based on the mentoring activities for the ability to write hijaiyah letters at TPQ Baiturrahman running smoothly with a very effective level of understanding of 20% and an effective 80% meaning that this activity was maximally successful.